1992
DOI: 10.1111/j.1471-0528.1992.tb13880.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin, atrial natriuretic peptide (ANP) and uterine and umbilical artery flow velocity waveforms in hypertensive pregnancies

Abstract: Objective To investigate the relation between concentrations of endothelin and atrial natriuretic peptide (ANP) in maternal plasma and vasospasm in the uterine and umbilical arteries as detected by duplex pulsed colour Doppler ultrasonography in hypertensive pregnancies.Design An observational study.Subjects 32 women admitted consecutively to hospital with pregnancy induced hypertension (seven without proteinuria and 25 with proteinuria) and 78 healthy pregnant women examined at 28–0 weeks ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…We and others have reported previously that plasma ET-1-LI levels in pregnant women with PIH are elevated compared with those in the normotensive pregnant women [5,11,13,17,20,28,32], although several investigators have reported contradictory results [3,16]. In the present study, ET-1-LI levels in the umbilical venous plasma of newborns from PIH women were also higher than those in newborns from normotensive pregnant women.…”
Section: Discussioncontrasting
confidence: 68%
“…We and others have reported previously that plasma ET-1-LI levels in pregnant women with PIH are elevated compared with those in the normotensive pregnant women [5,11,13,17,20,28,32], although several investigators have reported contradictory results [3,16]. In the present study, ET-1-LI levels in the umbilical venous plasma of newborns from PIH women were also higher than those in newborns from normotensive pregnant women.…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies have shown increased plasma ET-1 concentrations in preeclampsia [16][17][18][19], but some have failed to find such an association [20,21]. In one study [22], first trimester ET-1 levels could predict preeclampsia with high sensitivity.…”
Section: Et-1 Levels (Pg/ml)mentioning
confidence: 92%
“…In interference with relaxation factors, ET-1 plays an important role in regulating blood flow and blood pressure [17,18]. Previous reports on ET-1 concentrations in peripheral maternal plasma in patients with pre-eclampsia have been contradictory, some showing increased [4][5][6] and some normal values [7,8].…”
Section: Introductionmentioning
confidence: 98%